PkM pelatihan peningkatan usaha mikro dalam mewujudkan smart business melalui smartphone di masa pandemi Covid-19 - Reimond Hasangapan Mikkael; Helenia Touana; Muhammad Takrim (Penerbit Goodwood, 2020)
Purpose: This activity aims to help beginner and micro-business actors to take advantage of technology via smartphones during the Covid-19 pandemic. Method: This activity assists new and micro-business actors who have run the business. Results: The output of this dedication increases knowledge and expertise for Micro Business actors in choosing a suitable strategy in carrying out their business during the current Covid-19 pandemic. Conclusion: In this activity, 78 participants attended and the total participants who understood this training concept were as much as 65%. The remaining 35% of new MSME entrepreneurs still did not understand it because they were unfamiliar with an online business. Keywords: Business, Covid-19, Online, Smartphone, Training, MSME